Translanguaging in second language learning and writing in an adult english class (2018)
Studies on the benefits of the use of the first language in the development of second language writing have usually taken place in young bilingual students in countries in which they are immigrants or children of immigrants. This qualitative case study focused on young adult English learners in a language institute in Bogotá, Colombia; a context in which Spanish is the first language and English is learnt as a foreign language. Results on how the translanguaging phenomenon takes place in these students' L2 learning and writing were obtained through thematic coding of diverse forms of data: non-participant structured observations, semi-structured interviews, written samples, and an open-ended questionnaire. The findings revealed translanguaging was used as a learning and teaching strategy, as a strategy in second writing or biliteracy development, and as a psycholinguistic and sociolinguistic strategy. The study also proposes some considerations that should be taken into account when planning to implement translanguaging in a L2 class, so that students' learning process is enhanced by this phenomenon.